Geoffrey of Monmouth and the Feminist Origins of the Arthurian Legend - Tolhurst, F. author. aut Link
XI, 196 p.
Keywords: Geoffrey of Monmouth and the Feminist Origins of the Arthurian Legend provides the first feminist analysis of both the Arthurian section of The History of the Kings of Britain and The Life of Merlin .